Cobo, Rosa. Pornografía. El placer del poder. Barcelona, Ediciones B y Penguin Random House Grupo Editorial, 2020. ISBN: 978-84-666-6789-0. 206 páginas - Posada Kubissa, Luisa (Investigaciones Feministas, 2022)
Reseña de la obra de Cobo, Rosa. Pornografía. El placer del poder. Barcelona, Ediciones B y Penguin Random House Grupo Editorial, 2020. ISBN: 978-84-666-6789-0. 206 páginas